2022
DOI: 10.7759/cureus.29670
|View full text |Cite
|
Sign up to set email alerts
|

Education and Awareness Activities Regarding Hepatitis B and C Among Japanese Dental Health Workers in the Oita Prefecture

Abstract: Objectives: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infections are known to pose a major threat for dental health workers (DHWs). Previously, we reported that the HBV and HCV infection rates among DHWs in the Oita Prefecture in Japan were higher than those among the general population. The aim of this study was to disseminate knowledge about hepatitis and its prevention among the DHWs.Materials and Methods: Educational booklets were mailed to 2,197 DHWs working in 487 dental clinics. After anonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…We previously reported that the HBV infection rate in non-vaccinated Japanese DHCWs was about 16.9 times higher than that in vaccinated workers (Nagao et al, 2008). Our report showed that 98.5% of DHCWs remained uninfected by HBV after vaccine administration, whereas one in four non-vaccinated workers had a previous HBV infection (25.4%), characterized by HBsAg-negative and HB core antibody (anti-HBc)-positive serology, indicating a high infection rate (Nagao et al, 2008). Other reports also indicate a fivefold higher HBV infection rate among non-vaccinated individuals (Cleveland, 1996).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We previously reported that the HBV infection rate in non-vaccinated Japanese DHCWs was about 16.9 times higher than that in vaccinated workers (Nagao et al, 2008). Our report showed that 98.5% of DHCWs remained uninfected by HBV after vaccine administration, whereas one in four non-vaccinated workers had a previous HBV infection (25.4%), characterized by HBsAg-negative and HB core antibody (anti-HBc)-positive serology, indicating a high infection rate (Nagao et al, 2008). Other reports also indicate a fivefold higher HBV infection rate among non-vaccinated individuals (Cleveland, 1996).…”
Section: Discussionmentioning
confidence: 90%
“…In 2009, the Japanese Society for Infection Prevention and Control established the "Vaccine Guidelines for Healthcare Workers," which states that all healthcare professionals who may come in contact with patients, their blood, or environmental surfaces contaminated with blood should receive HB vaccination (Mikamo et al, 2020;Okabe et al, 2009). However, in one of our previous studies, we reported a high HBV infection rate and a low HBV vaccination rate among DHCWs in the Fukuoka prefecture in Japan (Nagao et al, 2008). Additionally, Tada et al (2014) reported that infection control practice was not widely practiced in dentistry in Japan.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations